MICROCREDIT AND UMKM EMPOWERMENT: A POLICY ANALYSIS BASED ON RECENT LITERATURE - Loso Judijanto; Tengku Hasan Basri (CV. Adiba Aisha Amira, 2024)
This study aims to analyse microcredit policy and its role in empowering Micro, Small and Medium Enterprises (MSMEs) based on recent literature. Microcredit has been recognised as an important instrument to improve access to finance for MSMEs that are often excluded from conventional banking services. This study reviews the impact of microcredit on MSME development, including the improvement of working capital, business expansion, and productivity and competitiveness. In addition to the benefits, the research also highlights the challenges in implementing microcredit policies, such as the risk of bad debts, low financial literacy, and limited infrastructure. In conclusion, more holistic and integrated policies involving synergies between the government, financial institutions, and non- governmental organisations are needed to create a sustainable MSME empowerment ecosystem.